Gradient Based Control and Synchronization of Lorenz System with Periodic Parametric Forcing - Khan, Mohammad Ali (Journal of Advanced Computer Science & Technology, 2012)
Several important properties of chaos synchronization with gradientbased control of chaotic system with periodic parametric forcing remainstill unexplored. This paper investigates the behavior of the Lorenz systemto change from chaotic to periodic, parametric forcing also entrainsthe system output with the forcing frequency. Secondly synchronizationof two identically chaotic Lorenz systems are derived by linear feedbackcontrol and then discussed the gradient based control method for Lorenzsystem with periodic parametric forcing. Finally numerical simulationresults are presented to show the feasibility and effectiveness of the approach.